1974
DOI: 10.1530/jrf.0.0390463
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Release in Cattle

Abstract: The cow has been specifically selected for lactational performance. It

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
54
1
2

Year Published

1979
1979
2000
2000

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(71 citation statements)
references
References 22 publications
(14 reference statements)
14
54
1
2
Order By: Relevance
“…The effect of daylength upon PRL levels has been reported by many other workers (see Karg and Schams, 1974) Trenkle, 1971b) although the nutritional effects were possibly ameliorated by increasing daylength during part of this experiment. Although there is controversy over the hypothesis that PRL is involved in the partition of nutrients between body weight and milk yield post-partum (Swan, 1976 ;Hart et al, 1978) …”
Section: Introductionsupporting
confidence: 80%
“…The effect of daylength upon PRL levels has been reported by many other workers (see Karg and Schams, 1974) Trenkle, 1971b) although the nutritional effects were possibly ameliorated by increasing daylength during part of this experiment. Although there is controversy over the hypothesis that PRL is involved in the partition of nutrients between body weight and milk yield post-partum (Swan, 1976 ;Hart et al, 1978) …”
Section: Introductionsupporting
confidence: 80%
“…Other authors have shown that the larger the number of teats, the higher the PRL release [14,30]. Suckling duration may have contributed to slightly higher plasma concentrations, because ewes with twins suckled their lambs for approximately two minutes longer than ewes with singles.…”
Section: Discussionmentioning
confidence: 98%
“…A distinct increase in peripheral blood concentrations of prolactin has been reported in relation to parturition in large domestic animals such as the cow (Hoffmann et al, 1973;Karg and Schams, 1974), sheep (Chamley et al, 1973;Kann and Denamur, 1974) and goat (Hart, 1972).…”
Section: Introductionmentioning
confidence: 98%